Porcelain Gallbladder: Often an Overlooked Entity - Iqbal, Sohail; Ahmad, Sarfraz; Saeed, Usman; Al-dabbagh, Mohammed (The Surgery Journal, 2017)
Background Porcelain gallbladder (GB) is a rare but potentially premalignant condition with minimal symptoms. Accident and Emergency (A&E) departments often tend to investigate abdominal pain through plain radiographs, which are occasionally reported by radiologists, thereby leaving behind few uncommon conditions, such as porcelain gallbladder unreported.Objectives We present three cases of porcelain GB in which initial diagnosis was not considered due to the presence of various other calcifications in the upper abdomen.Methods In A&E, plain abdominal X-rays were routinely performed in all three patients to investigate nonspecific postprandial abdominal pain. Although GB calcification was easy to diagnose on plain films, it was initially overlooked to be a cause of the symptoms and later was diagnosed on abdominal CT scans, performed for further evaluation.Results Abdominal X-rays revealed thin curvilinear calcification in the GB wall, partially calcified neck and body, and gall stones. CT scan confirmed porcelain GB in all three patients.Conclusion Gallbladder mural calcification is a rare cause of nonspecific abdominal pain, which is often overlooked on plain abdominal X-rays causing missed diagnosis. The association of porcelain GB with adenocarcinoma entails special emphasis on timely diagnosis and prompt management.
Keywords: porcelain gallbladder; cancer; diagnosis; mural calcification